2018
DOI: 10.1021/acs.energyfuels.7b03127
|View full text |Cite
|
Sign up to set email alerts
|

Ash Aerosol and Deposition Formation Mechanisms during Air/Oxy-combustion of Rice Husks in a 100 kW Combustor

Abstract: Pulverized rice husks are co-fired with natural gas in a 100 kW (rated) down-fired oxy-fuel combustor under two conditions: (1) air combustion (denoted as air) and (2) oxy-combustion with 70% O2 and 30% CO2 in the inlet oxidant gas (denoted as OXY70). Studied in this paper are (1) mechanisms governing the partitioning of inorganic matter within the fly ash aerosol and (2) how these affect mechanisms of deposition on heat transfer surfaces. In each case, the ash aerosol particle size distributions (PSDs) were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 28 publications
3
41
0
Order By: Relevance
“…The PSDs of these two rice husks are shown in Figure 2. The results from RH_US have been previously published, 15 and they are included in this paper for comparison purposes. The composition and ash analyses of both rice husks are shown in Tables 1 and 2, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The PSDs of these two rice husks are shown in Figure 2. The results from RH_US have been previously published, 15 and they are included in this paper for comparison purposes. The composition and ash analyses of both rice husks are shown in Tables 1 and 2, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…26−28 However, the experimental results from the authors of this paper suggested that there exists some extent of fouling tendency for rice husks co-firing with natural gas in a downfired combustor. 15 These discrepancies in ash partitioning and fouling behavior for rice husks may be caused by the variations in furnace type, the particle temperature history, and the ash properties of rice husks from different locations. Therefore, it is important to further conduct a systematical study on rice husk combustion to investigate the formation mechanism of ash aerosol and ash deposits.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, there exists increasing interest in pressurized oxy-fuel combustion technology because it can reduce the overall plant efficiency and reduce the CO 2 capture cost at the same time. The advantage of this technology has been validated by many researchers through both simulation methods , and experimental studies. A variety of research topics have been studied for atmospheric pressure oxy-combustion, such as (1) operating conditions, ignition, and flame stability, (2) heat transfer, emissivity, and thermal capacity of exhaust gases, (3) gaseous emissions and effects on pollution formation [NO x , SO 2 , and particulate matter (PM)], and (4) ash deposition and slagging and fouling on the wall and on the heat transfer surface. However, to the best knowledge of the authors, the PM formation from a pressurized oxy-fuel combustion process has not yet been reported. Studies concerning PM formation are necessary because it causes ash deposition on the heat transfer surface and may cause serious problems that threaten safety operation of the power plant. , Therefore, the target of this paper is to shed light on PM formation in pressurized oxy-fuel combustion.…”
Section: Introductionmentioning
confidence: 99%